The Evolution of Brand Preferences: Evidence from Consumer Migration - Bronnenberg, Bart J; Dubé, Jean-Pierre H; Gentzkow, Matthew (American Economic Review, 2012)
We study the long-run evolution of brand preferences, using new data on consumers' life histories and purchases of consumer packaged goods. Variation in where consumers have lived in the past allows us to isolate the causal effect of past experiences on current purchases, holding constant contemporaneous supply-side factors. We show that brand preferences form endogenously, are highly persistent, and explain 40 percent of geographic variation in market shares. Counterfactuals suggest that brand preferences create large entry barriers and durable advantages for incumbent firms and can explain the persistence of early-mover advantage over long periods. (JEL D12, L11, M31, M37)